Generation of KS-133 as a Novel Bicyclic Peptide with a Potent and Selective VIPR2 Antagonist Activity that Counteracts Cognitive Decline in a Mouse Model of Psychiatric Disorders - Sakamoto, Kotaro; Chen, Lu; Miyaoka, Tatsunori; Yamada, Mei; Masutani, Teruaki; Ishimoto, Kenji; Hino, Nobumasa; Nakagawa, Shinsaku; Asano, Satoshi; Ago, Yukio (Frontiers in Pharmacology, 2021)
Worldwide, more than 20 million people suffer from schizophrenia, but effective and definitive new therapeutic drugs/treatments have not been established. Vasoactive intestinal peptide receptor 2 (VIPR2) might be an attractive drug target for the treatment of schizophrenia because both preclinical and clinical studies have demonstrated a strong link between high expression/overactivation of VIPR2 and schizophrenia. Nevertheless, VIPR2-targeting drugs are not yet available. VIPR2 is a class-B G protein-coupled receptor that possesses high structural homology to its subtypes, vasoactive intestinal peptide receptor 1 (VIPR1) and pituitary adenylate cyclase-activating polypeptide type-1 receptor (PAC1). These biological and structural properties have made it difficult to discover small molecule drugs against VIPR2. In 2018, cyclic peptide VIpep-3, a VIPR2-selective antagonist, was reported. The aim of this study was to generate a VIpep-3 derivative for in vivo experiments. After amino acid substitution and structure optimization, we successfully generated KS-133 with (a) a VIPR2-selective and potent antagonistic activity, (b) at least 24 h of stability in plasma, and (c) in vivo pharmacological efficacies in a mouse model of psychiatric disorders through early postnatal activation of VIPR2. To the best of our knowledge, this is the first report of a VIPR2-selective antagonistic peptide that counteracts cognitive decline, a central feature of schizophrenia. KS-133 may contribute to studies and development of novel schizophrenia therapeutic drugs that target VIPR2.